2009
DOI: 10.1902/jop.2009.080502
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor–Mediated Treatment of Recession Defects: A Randomized Controlled Trial and Histologic and Microcomputed Tomography Examination

Abstract: CTG and rhPDGF-BB + beta-TCP + wound-healing dressing are effective treatment modalities for clinically correcting gingival recession defects. In addition, the current study demonstrated that regeneration of the periodontium in gingival recession defects was possible through a growth factor-mediated approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(138 citation statements)
references
References 15 publications
2
136
0
Order By: Relevance
“…However, occurrence of true regeneration after such procedures has been a controversial issue. McGuire et al [18] showed that no histological evidence of cementum, bone, or periodontal ligament (PDL) and, therefore, regeneration could be determined using CTG + CPF. Thus, they recommended adding some regenerative materials to enhance the capacity of tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, occurrence of true regeneration after such procedures has been a controversial issue. McGuire et al [18] showed that no histological evidence of cementum, bone, or periodontal ligament (PDL) and, therefore, regeneration could be determined using CTG + CPF. Thus, they recommended adding some regenerative materials to enhance the capacity of tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…New connective tissue attachment was also observed, including periodontal ligament. Majzoub et al/2001 [21]CTGLong junctional epithelium throughout the major portion. Only minimal signs of new cementum-like tissue Carnio et al/2002 [23]CTG + EMDShort junctional epithelium, dense CT fibers were found in close proximity to the root surface,No insertion of fibers into the root was observed.Newcementum and new bone in the most apical end of the grafted area. McGuire et al/2003 [10]CTGA connective tissue attachmentNo histological evidence of cementum, bone, or PDL. Cummings et al/2005 [24]CTGCementum deposition within the root notches, unaffected alveolar bone. McGuire et al/2009 [18]CTG + rhPDGF + beta-TCPEvidence of regeneration of cementum, PDL with inserting connective tissue fibers, and supporting alveolar bone, none of the CTG-treated sites exhibited any signs of periodontal regeneration. Roman et al/2010 [25]CTGNo ligament or bone, no sign of a long junctional epithelium a long connective tissue attachment…”
Section: Discussionmentioning
confidence: 99%
“…The use of recombinant growth factors has demonstrated regeneration histologically and by micro-computed tomography (CT) with Tricalcium Phosphate in randomized controlled clinical trials 22,23 .…”
Section: Platelet Rich Plasma and Platelet Derived Growth Factor (Pdgf)mentioning
confidence: 99%
“…The relapse in recession underscores the biological short-coming of connective tissue grafting for root coverage purposes, which results in a long-junctional epithelium compared with the more desirable outcome of periodontal regeneration (cementum, alveolar bone, and periodontal ligament). 2 She had undergone 2 previous periods of orthodontic treatment, during which teeth numbers 4 and 13 were extracted, and numbers 1 and 16 were retained (numbers 17 and 32 are retained and impacted). The resulting occlusion comprised an Angle class II molar relationship on the right (Fig.…”
Section: Dental Historymentioning
confidence: 99%